EFFICACY OF INTRA-ARTERIAL LIDOCAINE FOR PAIN CONTROL RESULTING FROM TRANSARTERIAL CHEMOEMBOLIZATION OF HEPATOCELLULAR CARCINOMA - Abbas, Ghulam; Sheraz, Atif; Rahim, Raza (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the efficacy of intra-arterial lidocaine in peri & post-procedural pain control and the dose of narcotic analgesic required in hepatocellular carcinoma patients undergoing transarterial chemoembolization.Study Design: Comparative prospective study.Place and Duration of Study: Armed Forces Institute of Radiology and Imaging Rawalpindi, from Jan to Jun 2019.Methodology: A total of 60 patients included in this study where 42 males and 18 were females, age range 45-85 years who underwent transarterial chemoembolization for hepatocellular carcinoma, were included in the study. patients were equally divided into two groups, group a (30 patients) who underwent transarterial chemoembolization, received 60 mg of intraarterial lidocaine each and group b (30 patients) who underwent transarterial chemoembolization, intra-arterial lidocaine was substituted with normal saline.degree of post-procedural pain was assessed using a subjective method (visual analogue scales score) and an objective method (amount of post-procedural analgesics).Results: Average peri-procedure visual analogue scale score was 5.06 in group A patient versus 7.2 for those in group B patients (p=0.037). Post-procedure visual analogue scale score in the group A was 2.7 ± 0.520 and that for group B was 4.2 ± 0.761 (p=0.025). Mean of total dose of nalbuphine in group A was 4.96 ± 0.764 mg versus 8.3 ± 1.34 mg for patients in group B (p=0.036). Average length of post procedure hospital stay was 0.9 ± 0.203 and 1.41 ± 0.373 days for group A and group B respectively (p=0.002).Conclusion: Intra-arterial administration of lidocaine before infusing the embolization particles for transarterial chemoembolization.....................